Reforming agricultural markets in Africa: achievements and challenges - Kherallah, Mylene; Delgado, Christopher L.; Gabre-Madhin, Eleni Zaude; Minot, Nicholas; Johnson, Michael E. (Johns Hopkins University Press, 2002)
The long-term reduction of hunger and poverty in Sub-Saharan Africa remains one of the great challenges for the international development community. Eliminating hunger and promoting widespread growth in the region inevitably involves agriculture, given its central role in the region's economies. Over the past 20 years, most African governments have carried out reforms to deregulate agricultural markets and reduce the role of state enterprises. How much has the state actually withdrawn from agricultural markets? Have well-functioning private markets emerged? How successful were these reforms in boosting agricultural production, economic growth, and the incomes of the rural poor? What lessons can we learn from the reform process? The authors of this book address these questions through an analysis based on an extensive review of experiences with reform, focusing on three major agricultural markets: fertilizer, food crops, and export crops. They examine the historical rationales for intervention, the factors contributing to reform, the process of implementation, and the impact of the reforms on farmers and consumers in Sub-Saharan Africa. The authors find that reforms have had many favorable results, but that the impact has been muted by partial implementation and structural constraints. They propose a new agenda for promoting the development of agricultural markets in Sub-Saharan Africa, identifying areas where governments can play a supportive role. They argue that appropriate agricultural marketing policies and investments can improve livelihoods and the economic health of the region. -- From 'About this Book'"